The Relationship between Role of Drug Supervisor (PMO) with Successful Treatment of Pulmonary Tuberculosis Patients in Working Area Sukamerindu Public Health Center Bengkulu - Suryani Suryani; S. Effendi; Refin Herizon (Jurnal Sains Kesehatan, 2018)
The impact and dangers  of  Pulmonary Tuberculosis  incidence is causing death. In Bengkulu province in 2011 there were 1.565 cases of  pulmonary  tuberculosis in 2012  there were 1,670 cases of pulmonary tuberculosis in 2013 there were 2.671 cases of pulmonary tuberculosis and in 2014 there were 2.014 cases of pulmonary tuberculosis this showed that pulmonary tuberculosis was still high. The purpose of this study was to study the relationship of PMO role with                         the success of the treatment of pulmonary tuberculosis patients in working area of Sukamerindu Public Health Center Bengkulu. The type of research used was                 an analytic survey, with Cross Sectional research design. Population in this research was all patient of pulmonary tuberculosis in working area of  Sukamerindu Public Health Center Bengkulu which had treatment 5 months amounted to 36 people in 2015. Samples taken by using total sampling which amounted to 36 people. Data analysis was done by univariate and bivariate analysis using uni Chi-Square (χ2). The results of this study were 41 patients with pulmonary tuberculosis,  20 people (55.6%)  had good role of  PMO, and there were 30 people (83.3%) who had successful treatment, there was a significant relationship between the role of PMO with successful treatment of patients with pulmonary tuberculosis with moderate category. It was  suggested to the related institution to improve and supervise the cadre of  (PMO) so that the success of   the treatment of pulmonary tuberculosis will  increasing. Keywords : drug  supervisor (PMO), successful  treatment, pulmonary  tuberculosis  patients